2017
DOI: 10.1186/s13068-017-0814-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced biomethane production rate and yield from lignocellulosic ensiled forage ley by in situ anaerobic digestion treatment with endogenous cellulolytic enzymes

Abstract: BackgroundEnzymatic treatment of lignocellulosic material for increased biogas production has so far focused on pretreatment methods. However, often combinations of enzymes and different physicochemical treatments are necessary to achieve a desired effect. This need for additional energy and chemicals compromises the rationale of using enzymes for low energy treatment to promote biogas production. Therefore, simpler and less energy intensive in situ anaerobic digester treatment with enzymes is desirable. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 33 publications
1
18
0
1
Order By: Relevance
“…10 ml of cooled extraction buffer (2× [50 mM Tris–HCl, pH 8,5, 5 mM EDTA, 100 mM KCl, 1% (w/v) DTT, 30% (w/v) sucrose]), containing the cOmplete protease inhibitor mix (Roche) were added to the 10-ml concentrated sample [24]. After vortexing, protein samples were extracted with 10 ml Tris-buffered phenol, pH 8.0 (Sigma, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…10 ml of cooled extraction buffer (2× [50 mM Tris–HCl, pH 8,5, 5 mM EDTA, 100 mM KCl, 1% (w/v) DTT, 30% (w/v) sucrose]), containing the cOmplete protease inhibitor mix (Roche) were added to the 10-ml concentrated sample [24]. After vortexing, protein samples were extracted with 10 ml Tris-buffered phenol, pH 8.0 (Sigma, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown promising results with regard to increased hydrolysis as well as increased biogas production due to the addition of enzymes [87]. Enhancing the degradation of lignocellulosic substances using enzymes that degrade lignin, cellulose, and other polysaccharides has been the focus of enzymatic treatment studies.…”
Section: Treatment Strategies For Particle-rich Substratesmentioning
confidence: 99%
“…dX C dt = −K h S surf (8) where S surf is the surface area of solid particulates and ρ solid is the density of solid particulates. Various authors report that Contois kinetics provides a better fit for AD of complex substrates compared to first-order kinetics [86][87][88]. Contois kinetics (Equation (9)) takes effects of active biomass (X biom ) and its ratio to the slowly degradable substances (Xc) in the substrate into account.…”
mentioning
confidence: 99%
“…show that combined processes are high energy-consuming methods(Gumisiriza et al, 2017;Speda et al, 2017;Perendeci et al, 2018). High temperatures and limited heat recovery during steam explosion (SE) pretreatment may lead to high energy use and reduced methane yield(Gumisiriza et al, 2017).…”
mentioning
confidence: 99%